Among landscapes: local history and museological communication in north-eastern São Paulo State. (Cadernos de Sociomuseologia, 2025)
The research consists of an analysis of the way in which the historical museums in the immediate region of Ribeirão Preto, in the countryside of the State of São Paulo, Brazil, represent the different migrant populations in their collections and in their museological communications. Sixteen historical museums located in eleven cities of the selected space were analyzed. The research was carried out in a qualitative-quantity manner, consisting of direct observation, document analysis, questionnaires and interviews. The research hypothesis is that the historical museums of the selected region do not represent the populations that were enslaved in the region in the 19th century, as well as they do not represent migrants from the north and northeast regions of the country in their collections and permanent exhibitions, even though the region of Ribeirão Preto has attracted, over the previous two centuries, thousands of people to work in the coffee sector and, later, in the sugar cane sector. As a result, the ideas of